Evaluación técnica de la etapa coagulación-floculación para el mejoramiento en el proceso de potabilización de la planta galán de la EAAAZ (2017)
For the Aquaculture, Sewer and Toilet Company of Zipaquirá (EAAAZ) to be able to supply drinking water to about a third of the population of the municipality uses as a surface water adduction to the Frio River for the most part and as a backup source of the streams The Borrachero, the Hoya and the Artesa; Which arrive at the Galán plant to be able to have the necessary treatments and guarantee the water supply to the population, where the steps of coagulation, flocculation, filtration, disinfection and pH stabilization are carried out in order to obtain good quality water And which lead to compliance with established national standards such as resolution 2115 of 2007 for drinking water. In order to comply with the development of the technical evaluation of the coagulation-flocculation stages applied at the Galán plant of EAAAZ, the current operation of the plant has been inspected, together with the pertinent information supplied by the company, a general diagnosis of the Process stages for the potabilization of raw water together with technical specifications of the equipment and current dosages used by the company.